Manajemen Risiko Keselamatan Dan Kesehatan Kerja (K3) Pada Pekerja Penambang Pasir Kali Dentunura Kecamatan Nangaroro Kabupaten Nagekeo - Meo, Yohanes; Gado, Alfridus (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2021)
Sand mining workers are part of the procurement of materials for construction activities, so they need to beconsidered because the risk opportunities are quite large. In this study, the risk assessment method uses arisk assessment matrix. After collecting the data, it is then analyzed to find out how big the risk is to the sandmining workers of the Ventura River. The results of this study obtained that the risk due to employees(workers) having received assistance index 6.06, moderate risk category, risk due to accidents to employees(workers) index 11.34 very high-risk category, risk due to using index tool 11.01 very risk category. high risk,material, and dust risk index 14.82, including very high-risk category, risk due to bad weather index 12.96,very high-risk category, risk index due to accidental fracture of legs and arms 7.53, included in the high-riskcategory, risk due to helping employees during an accident index 9.60, very high-risk category, risk due tousing personal protection index 5.83, moderate risk category, risk due to explanations related to safety andhealth. index 6.36, moderate risk category, risk due to explanation sand excavation technique index 4.47,moderate risk category. The average index risk index is 8.99 including high risk. In the activities of sandmining workers and construction work activities, they must first identify and analyze the level of risk.